Triglycerides and leptin soluble receptor: Which one is the target to protect β-cells in patients with type 2 diabetes? - Alzamil, Hana; Aldokhi, Laila (Frontiers in Endocrinology, 2023)
Objectives: to study the relationships of leptin and leptin SR with adiposity indices, and glycemic indices in patients with type 2 diabetes mellitus (T2DM) compared to healthy subjects. Methods: This cross-sectional study involved 65 patients with T2DM and 63 healthy controls. Fasting plasma levels of leptin, leptin SR, insulin and lipid profile were measured by enzyme linked immunosorbent essay, basal insulin resistance and beta-cell function were assessed using the homeostasis model assessment. Results: leptin SR level was significantly higher in T2DM patients than in controls (5.8 ± 1.6 and 4.8 ± 1.3 respectively; p= 0.001). In patients with T2DM, leptin SR was negatively correlated with homeostasis model of β-cell function and body fat mass while it has a significant positive correlation with glycosylated hemoglobin (HbA1c). The independent predictors for leptin SR in patients with T2DM were triglycerides (TG) and HbA1c. Conclusions: elevated serum leptin SR level in patients with T2DM was positively correlated with TG and abnormal glucose metabolism which indicate that it plays a role in pathophysiology of T2DM. The association of elevated leptin SR level with high TG and deterioration of β-cell function indicate that in some individuals, particularly non-obese, dyslipidemia might be a cause rather than a complication of diabetes.